Context Matters: Violence Against Women and Reporting to Police in Rural, Suburban and Urban Areas - Rennison, Callie Marie (American journal of criminal justice, 2013)
Despite plentiful efforts to identify perpetrator, victim, and incident characteristics correlated with reporting violence against women to police, few studies have addressed the contexts that shape such reporting. Even fewer have examined variations in these contexts across geographic areas. Drawing upon National Crime Victimization Survey data from 1992 through 2009, this paper uses conjunctive analysis of case configurations to identify and investigate the dominant situational contexts of reporting of violence against women to police across rural, suburban, and urban areas. Our findings show that context matters and the importance of incident, perpetrator, and victim characteristics vary across geographic areas.